Unfruitful Expenditure on Non-Functional Trauma Care Centres in Gujarat - CAG of India (CAG of India)
Trauma Care Centre established at a cost of INR 1.59 crore could not be put to use due to non-appointment of Medical and Para-Medical Staff.